Conservation of isolated Atlantic heathlands in the Mediterranean region: effects of land-use changes in the Montseny biosphere reserve (Spain) - Bartolomé, Jordi; Plaixats, Josefina; Fanlo, Rosario; Boada, Martí (Biological Conservation, 2005)
In the Mediterranean region, cycles of controlled burning combined with continuous grazing appear to have been an effective tool for maintaining isolated Calluna vulgaris heathlands in the form in which they occur in many places in the Atlantic region. Changes in land use and management of the mosaic of extensively exploited heathland and associated grassland over recent decades, such as bringing land into cultivation followed by its abandonment and the prohibition of fires has resulted in a process of transformation into new shrub communities with lower biodiversity. In the Mediterranean region, these changes are similar to those described in the Atlantic area, but encroachment occurs faster and could lead ultimately to afforestation by Mediterranean woodland.
Keywords: calluna vulgaris; fire; grassland; Grazing; landscape

Conservation of isolated Atlantic heathlands in the Mediterranean region: effects of land-use changes in the Montseny biosphere reserve (Spain) - Bartolomé, Jordi; Plaixats, Josefina; Fanlo, Rosario; Boada, Martí (Biological Conservation, 2005)
In the Mediterranean region, cycles of controlled burning combined with continuous grazing appear to have been an effective tool for maintaining isolated Calluna vulgaris heathlands in the form in which they occur in many places in the Atlantic region. Changes in land use and management of the mosaic of extensively exploited heathland and associated grassland over recent decades, such as bringing land into cultivation followed by its abandonment and the prohibition of fires has resulted in a process of transformation into new shrub communities with lower biodiversity. In the Mediterranean region, these changes are similar to those described in the Atlantic area, but encroachment occurs faster and could lead ultimately to afforestation by Mediterranean woodland.
Keywords: calluna vulgaris; fire; grassland; Grazing; landscape

Grazing alone is not enough to maintain landscape diversity in the Montseny Biosphere Reserve - Bartolomé, J.; Franch, J. (Agriculture, Ecosystems & Environment, 2000)
Conservative land-use over the past few decades has converted the Montseny Biosphere Reserve (Spain) from the original open, patchy landscape to almost continuous woodland. Small ruminant grazing is virtually the only major remaining utilisation activity yet little is known about its role in the changing vegetation of the Reserve. This study was undertaken to determine the effects of current grazing practice on its main vegetation components. Three ﬂocks, composed of sheep and goats, that graze yearlong on three separate ranges in the Reserve were selected for study. The ranges represent the wooded slopes and the shrubby upland (altiplano) in the area. Biomass consumption by the ﬂocks was estimated by calculation of normative requirements for observed production and the botanical composition of the livestock diets over a whole annual cycle was determined by micro-histological analysis of the faeces. Production of herbaceous vegetation was determined by clipping sample quadrats, the production of the woody vegetation was derived from previous work in the Reserve. It was found that grazing removed a very small proportion of the dominant Holm oak (Quercus ilex) on the slopes, and a moderate fraction of the shrubby and herbaceous vegetation on the altiplano. Only the heath tree (Erica arborea), an edible shrub in the woodlands, was relatively heavily grazed. It is concluded that grazing alone is not enough to maintain the open, diverse landscape with its many natural values. As in other northern Mediterranean countries, under-utilisation of these woodlands is becoming a serious problem that is also increasing the ﬁre hazard. Maintaining landscape diversity in the region is a complex challenge that land managers should recognise
Keywords: calluna vulgaris; Erica arborea; mediterranean rangeland; Quercus ilex; small ruminants

Grazing alone is not enough to maintain landscape diversity in the Montseny Biosphere Reserve - Bartolomé, J; Franch, J (Agriculture, Ecosystems & Environment, 2000)
Conservative land-use over the past few decades has converted the Montseny Biosphere Reserve (Spain) from the original open, patchy landscape to almost continuous woodland. Small ruminant grazing is virtually the only major remaining utilisation activity yet little is known about its role in the changing vegetation of the Reserve. This study was undertaken to determine the effects of current grazing practice on its main vegetation components. Three ﬂocks, composed of sheep and goats, that graze yearlong on three separate ranges in the Reserve were selected for study. The ranges represent the wooded slopes and the shrubby upland (altiplano) in the area. Biomass consumption by the ﬂocks was estimated by calculation of normative requirements for observed production and the botanical composition of the livestock diets over a whole annual cycle was determined by micro-histological analysis of the faeces. Production of herbaceous vegetation was determined by clipping sample quadrats, the production of the woody vegetation was derived from previous work in the Reserve. It was found that grazing removed a very small proportion of the dominant Holm oak (Quercus ilex) on the slopes, and a moderate fraction of the shrubby and herbaceous vegetation on the altiplano. Only the heath tree (Erica arborea), an edible shrub in the woodlands, was relatively heavily grazed. It is concluded that grazing alone is not enough to maintain the open, diverse landscape with its many natural values. As in other northern Mediterranean countries, under-utilisation of these woodlands is becoming a serious problem that is also increasing the ﬁre hazard. Maintaining landscape diversity in the region is a complex challenge that land managers should recognise
Keywords: calluna vulgaris; Erica arborea; mediterranean rangeland; Quercus ilex; small ruminants

Diet selection by sheep and goats on Mediterranean heath-woodland range - Bartolomé, J; Franch, J; Plaixats, J; Seligman, N G (JOURNAL OF RANGE MANAGEMENT, 1998)
The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Animals grazed a mountain rangeland composed of Qeurcus ilex woodland and Calluna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both sheep and goat. Of these, 23 were represented in proportions of more than 1% of the annual diet. Even though goats and sheep grazed together, their diets were significantly different (p < 0.0001), the animal factor accounting for 18% to 60% of the total variation among the main diet components. Variation between seasons was also a major (5% to 56%) highly significant factor, while differences between flocks accounted for a significant, but relatively small part (3% to 10%) of the total variation in diet. The outstanding difference was the avoidance of the tree, Quercus ilex, by the sheep while the goats selected it throughout the year. Sheep selected graminoids throughout the year while goats tended to avoid them. For the rest there.was substantial overlap in species composition between the diet of sheep and goats, especially when analysed over an entire cycle.
Keywords: calluna vulgaris; Erica arborea; fecal analysis; microhistological analysis; Quercus ilex

Diet selection by sheep and goats on Mediterranean heath-woodland range - Bartolomé, J.; Franch, J.; Plaixats, J.; Seligman, N. G. (JOURNAL OF RANGE MANAGEMENT, 1998)
The study determined the species components of the diets of small ruminants grazing mountain ranges of the Montseny Biosphere Reserve (Catalunya, NE Spain). Three mixed flocks of sheep and goats, led by shepherds, were monitored for a year. Animals grazed a mountain rangeland composed of Qeurcus ilex woodland and Calluna-Erica heathland during the day and were returned to their corrals every night. Diet selection was estimated using fecal analysis. Of the 111 species that were identified, 71 were common to both sheep and goat. Of these, 23 were represented in proportions of more than 1% of the annual diet. Even though goats and sheep grazed together, their diets were significantly different (p < 0.0001), the animal factor accounting for 18% to 60% of the total variation among the main diet components. Variation between seasons was also a major (5% to 56%) highly significant factor, while differences between flocks accounted for a significant, but relatively small part (3% to 10%) of the total variation in diet. The outstanding difference was the avoidance of the tree, Quercus ilex, by the sheep while the goats selected it throughout the year. Sheep selected graminoids throughout the year while goats tended to avoid them. For the rest there.was substantial overlap in species composition between the diet of sheep and goats, especially when analysed over an entire cycle.
The following values have no corresponding Zotero field: pub-location: 445 UNION BLVD, STE 230, LAKEWOOD, CO 80228-1259 USA publisher: SOC RANGE MANAGEMENT
Keywords: calluna vulgaris; Erica arborea; fecal analysis; microhistological analysis; Quercus ilex